Molecular Analysis of Oxacillinase Genes in MDR strain of Acinetobacter baumannii and Comparative evaluation of Vitek 2 and Broth micro dilution method for Colistin Susceptibility testing isolated in clinical sample from North India - Pandey, Anand Kumar; Siddiqui, Areena Hoda; Saquib, Mohd; Srivastava, Vipul Kumar; Tiwari, Neha (Journal of Neonatal Surgery, 2025)
Background: Performances of the Colistin antimicrobial susceptibility testing (AST) systems of Acinetobacter baumannii vary depending on the manufacturer, and data on Colistin-resistant A. baumannii are limited. We evaluated the VITEK2 and Sensititre systems to determine Colistin resistance and minimum inhibitory concentration (MIC) for A. baumannii isolated from a clinical microbiology laboratory. A total of 88 clinical A. baumannii isolates were tested, including 14 Colistin-resistant A. baumannii. ASTs were performed using the VITEK2 according to the manufacturer’s instructions. Reference MICs for Colistin were determined using the manual broth micro dilution method (BMD). The results of AST methods were compared with the BMD results. Material Methods: Clinical samples received for bacterial culture and antimicrobial sensitivity testing were inoculated and incubated for 24-48 hours at 37°C. For blood culture incubation was done for 5 days in blood culture bottle. Bacterial identification and antimicrobial sensitivity were done by Vitek®2, bioMérieux. Antimicrobial Sensitivity of A. baumannii isolated was recorded and multi drug resistant isolates were preserved for Polymerase chain reaction (PCR) to detect the presence offbeat lactam Oxacillinase blaOXA 51 and blaOXA58 genes. Result: In total 2644 samples were processed during the study period from 30th April, 2022 to 20th October, 2024. 920 samples were culture positive. Out of 920 bacterial isolates, 88 were A. baumannii and 84 out of these were Carbapenem Resistant A. baumannii (CRAB). 54 CRAB isolates were for PCR and all showed presence of blaOXA 51 genes while none of the isolates harbored blaOXA 58 genes. Conclusion: There is an increased isolation rate of A. baumannii from clinical samples and more than 95% isolates of A. baumannii are CRAB. All the CRAB isolates tested by PCR showed presence of blaOXA 51 genes and none had the presence of blaOXA 58 genes. Management of A. baumannii infections is a challenge. In the current scenario proper implementation of Hospital Infection Control policies and adherence to antimicrobial stewardship policies as preventive strategies should be our priority.This study highlights that the high frequency of isolation of Carbapenem-resistant Acinetobacter baumannii strain in high-risk infectious wards requires an accurate application of methods for detecting susceptibility to antibiotics, in particular to Colistin, so as the correct therapeutic approach. As the frequency of resistance Colistin is low, it can be used as an easily available drug for Carbapenem resistance Acinetobacter baumannii strains which are susceptible to Colistin